Neuromuscular adaptations to different set configurations during a periodized power training block in elite junior Judokas - Harris, D. M.; Oranchuk, D. J.; Latella, C. (International Journal of Sports Science & Coaching, 2024)
Although the impacts of traditional sets (TS) versus cluster (CL) sets resistance training have been broadly explored among recreationally trained populations, no studies have previously compared these set configurations among elite Judokas. Twenty-two elite male and female Judokas (age = 17.5 ± 1.2 years) performed identical periodized 4-week hypertrophy and strength blocks (8 weeks in total). Following this, for the final 4-week power training block, the cohort was separated into either TS (n = 11) or CL (n = 11) set structures. CL were prescribed by including 45-second intra-set rest every two repetitions. One-repetition maximum (1RM) and peak barbell velocities of the back squat and bench press, and countermovement (CMJ) jump height were assessed before and following each 4-week mesocycle. Significant strength and power improvements were observed after the 4-week hypertrophy training block (1RM bench press = delta3.82 kg, ES [95% CI] = 1.34 [0.76, 1.93], p < 0.001; 1RM squat = delta4.71 kg, ES = 0.52 [0.07, 0.96], p = 0.024; CMJ height = delta0.54 cm, ES = 0.62 [0.16, 1.07], p = 0.008) and after the 4-week maximal strength training block (1RM bench press = delta1.5 kg, ES = 0.68 [0.21, 1.41], p = 0.004; 1RM squat = delta5.47 kg, ES = 0.61 [0.15, 1.06], p = 0.010; CMJ height = delta0.45 cm, ES = 0.71 [0.23, 1.17], p = 0.003). However, no time × group differences were observed between the TS and CL groups following the 4-week power training block. Though traditional periodized resistance training improved neuromuscular qualities of elite junior Judokas, no between-group neuromuscular differences using either TS or CL suggests that both methods may be used as part of periodized training programs.